Application of XPS and PA techniques in the study of lime used in the Talavera House from the historical center of Mexico City (Superficies y Vacío, 2021)
X-ray Photoelectron Spectroscopy (XPS) and Photoacoustic (PA) techniques are useful to identify the structure and optical properties of chemical compounds used in archaeology, among others. In the present study XPS and PA techniques were used to analyze seven samples obtained from the Talavera House, during the conservation and restoration works carried out in the 2012-2013 period. Talavera House is located between the República del Salvador, Talavera and Roldán streets, in the historic center of Mexico City. The objective of this study was to identify the chemical compounds added to the lime when burned in the furnace and its use in the tanneries during the 18th century, both elements located in the second yard, as well as in the construction of the corridor in the 20th century located in the first courtyard. The samples were collected at these points and analyzed by XPS and Photoacoustic (PA) techniques, comparing these results with other excavated sites.